Papermaking additive based on nanocellulose as well as preparation and application methods thereof
By forming a crosslinking network between nanocellulose and filler in papermaking additives, the problem that nanocellulose in the prior art is difficult to improve the retention rate and paper mechanical properties of the filler at low doses is solved, and efficient retention and enhancement effects are achieved.
Patent Information
- Application Number
- CN202510026229.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-28
AI Technical Summary
When existing nanocellulose is used as papermaking additives, it is difficult to simultaneously improve the filler retention rate and paper mechanical properties at low doses.
By forming a preliminary flocculant with the filler and forming a crosslinking network under the action of the crosslinking agent, nanocellulose-coated filler particles are formed to enhance the binding with the pulp fibers.
It has achieved the improvement of filler retention rate and paper mechanical properties at a lower dosage, solved the problem that traditional nanocellulose is difficult to form a continuous network structure, and simplified the application process of papermaking additives.
Smart Images

Figure CN119711243A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of nanocellulose, and in particular to a papermaking auxiliary agent based on nanocellulose and a preparation and application method thereof. Background Art
[0002] Fillers can reduce the amount of pulp used, increase the density of paper structure, and provide functions such as improving opacity and printing performance in the papermaking process. Therefore, fillers have become an important raw material in the papermaking process. Currently, most functional fillers on the market are minerals, such as titanium dioxide, magnesium hydroxide, zeolite, and calcium carbonate. These functional fillers can replace more than 30% of pulp fibers in the final paper products due to their wide range of usage and low cost. However, their fine particle size and poor binding ability with pulp fibers lead to two significant disadvantages: 1) low filler retention rate because fillers are easily lost through the screen, and 2) because they will destroy the bonding between pulp fibers, which will lead to a significant decrease in the mechanical properties of the final product.
[0003] In order to improve the filler retention rate, filler pre-flocculation technology has been developed to produce large particles to enhance the interfacial bonding between pulp fibers and fillers and improve the mechanical retention between fillers and fibers. However, due to the obvious decrease in mechanical properties, reinforcing agents such as starch, polyacrylamide (PAM) and carboxymethyl cellulose (CMC) are often required to compensate for the mechanical loss of paper due to the introduction of a large amount of fillers. Therefore, there is an urgent need to develop biomass-based biodegradable additives that can simultaneously improve retention and paper strength.
[0004] Cellulose nanofibers (CNFs) are a new type of papermaking aid. As the smallest structural component of plant cell walls, CNFs can be prepared through the mechanical dissociation process of plant fibers. CNFs have many unique characteristics: such as nanoscale size (width <20 nanometers, length >1 micron), high aspect ratio and high mechanical properties (Young's modulus of the crystal region >130GPa, strength >2-6GPa), which enables CNFs to assemble into a network structure during the filtration process and form a tightly packed paper structure after drying. Therefore, combined with the high compatibility of pulp fibers, the distribution of CNFs in pulp fibers can be used as a reinforcing filler and can be used as a retaining and reinforcing agent.
[0005] Chinese patent CN117604812A discloses a method for preparing a high-efficiency reinforcing retention agent containing nanocellulose and its application in papermaking. The reinforcing retention agent is obtained by using nanocellulose as a skeleton and adding starch, a cationic agent, a reinforcing agent and other modifying agents. However, the process operation is complicated and a large number of additives are added, which is not conducive to industrialization. In addition, the reinforcing agent needs to be added later, and it is impossible to achieve the effect of one agent simultaneously reinforcing the paper and acting as a retention filler.
[0006] Chinese patent CN111138719A discloses a method for preparing a powder containing nanocellulose, wherein a nanocellulose aqueous dispersion is mixed with one or more of starch, calcium carbonate, and kaolin and a plasticizer is added. After drying, the nanocellulose powder is mechanically crushed and sieved to obtain a powder containing nanocellulose with a high solid content, which can be used in the field of paper addition. However, simply adding a plasticizer cannot guarantee that the paper can be strengthened, and the process requires drying the block and then crushing and sieving the powder, which is a cumbersome process and cannot be directly used for paper addition.
[0007] Chinese patent CN104343043B discloses a process for producing a ground calcium carbonate suspension, which is obtained by mixing the calcium carbonate to be ground with a nanocellulose solution and grinding it. The process disperses calcium carbonate with nanocellulose instead of polyacrylic acid and other substances, reducing the harm of polyacrylic acid and other substances to the human body. The process produces calcium carbonate with a small particle size to improve the dispersion of calcium carbonate, resulting in a low calcium carbonate retention rate, which cannot comply with the industry trend of high paper filling.
[0008] In summary, the current nanocellulose used as a retention filler still cannot achieve the effect of both filler retention rate and paper mechanical properties at a low dosage. Summary of the invention
[0009] The object of the present invention is to provide a papermaking auxiliary agent based on nanocellulose and a preparation and application method thereof, which can achieve the improvement of filler retention rate and paper mechanical properties at the same time with a lower dosage.
[0010] To achieve the above objectives, the present technical solution provides a method for preparing a papermaking aid based on nanocellulose, comprising the following steps:
[0011] Diluting the nanocellulose solution to a target concentration, and then adding filler powder to the cellulose nanosolution to obtain a target mixed solution;
[0012] A crosslinking agent solution is added to the mixed solution and stirred uniformly to obtain a papermaking additive based on nanocellulose, wherein the crosslinking agent in the crosslinking agent solution includes metal ions that provide empty coordination orbitals for chelating with polar groups on the nanocellulose to enhance the performance of the paper additive.
[0013] After the nanocellulose and filler in this solution are uniformly mixed, the nanocellulose forms coordination adsorption between the filler particles and the metal ions on the particle surface to form a preliminary flocculent, and then a cross-linking agent is added to the preliminary flocculent, and the cross-linking agent fixes the nanocellulose that is not coordinated with the filler to form an intermediate flocculent, and the intermediate flocculent is uniformly stirred and dispersed to obtain a filler-cellulose nanofiber material of uniform size as a papermaking aid based on nanocellulose. The papermaking aid based on nanocellulose prepared in this solution can be directly added to pulp without the need for drying and crushing operations.
[0014] It should be noted that due to the small size of nanocellulose, it is unable to form a continuous network structure in paper. Therefore, in order to achieve sufficient reinforcing performance, it is often necessary to add a higher amount of nanocellulose. However, the high price of nanocellulose has hindered industrial development. The nanocellulose provided in this solution first forms a preliminary flocculent with the filler, and after further adding a cross-linking agent, a cross-linked network can be formed in the filler. The final filler is wrapped with nanocellulose on the outside, so it can be fully combined with pulp fibers. The resulting paper has a high filler retention rate, and simultaneous retention of nanocellulose and filler is achieved, thereby improving the problem that traditional cellulose nanofibers are less retained in paper and difficult to form a continuous network structure.
[0015] In some embodiments, the surface of the nanocellulose in the nanocellulose suspension is rich in functional groups that can coordinate with metal ions, such as enzymatically hydrolyzed cellulose nanofibers, acid-hydrolyzed cellulose nanofibers, APS-oxidized cellulose nanofibers, TEMPO-oxidized cellulose nanofibers, carboxymethylated cellulose nanofibers, periodate-oxidized cellulose nanofibers, maleic anhydride-esterified cellulose nanofibers, and phosphorylated cellulose nanofibers. One or a combination of several.
[0016] Preferably, the nanocellulose in the nanocellulose suspension is selected as a cellulose nanofiber with a high charge, or is selected from one or more combinations of TEMPO oxidized cellulose nanofibers and carboxymethylated cellulose nanofibers, periodate oxidized cellulose nanofibers, maleic anhydride esterified cellulose nanofibers, and phosphorylated cellulose nanofibers. The advantage of selecting a cellulose nanofiber with a high charge is that the cellulose nanofiber with a high charge has high crystallinity, good strength, high aspect ratio, and rich functional groups on the surface that can coordinate with metal ions.
[0017] In some embodiments, the length to diameter ratio of the nanocellulose in the nanocellulose suspension is greater than 150, and the diameter is less than 20 nm. The advantage of this is that nanocellulose with a higher aspect ratio is more conducive to coating flocculation fillers and can better strengthen paper.
[0018] In some embodiments, the nanocellulose suspension has a cellulose concentration of (0.02-3.5 g) / 100 mL of water.
[0019] In some embodiments, the filler in the filler suspension is selected from one or a combination of calcium carbonate, magnesium carbonate, talc, titanium dioxide, calcium silicate, barium sulfate, dolomite, white carbon black, bentonite, polymer particles, zeolite, gypsum, vermiculite, sepiolite, diatomaceous earth, halloysite, tremolite, magnesium hydroxide, aluminum hydroxide, and kaolin.
[0020] In some embodiments, the filler concentration in the filler suspension is (0.1-50) g / 100 mL water.
[0021] In some embodiments, the ratio of cellulose in the nanocellulose suspension to filler in the filler suspension is 1:40.
[0022] In some embodiments, the nanocellulose suspension is mixed with a filler to obtain a mixed solution, which is a flocculent suspension containing preliminary floccules, and the mixing method is selected from one or a combination of mechanical stirring, magnetic stirring, ultrasonic mixing, bubbling mixing, high-pressure homogenization, and convection mixing.
[0023] In some specific embodiments, the nanocellulose suspension and the filler suspension are shear mixed at 3000-30000 r / min for 0.5-10 min to obtain a mixed solution.
[0024] In some embodiments, the crosslinking agent of the present embodiment is selected from a transition metal ion or an alkaline earth metal ion, both of which can provide an empty coordination orbital to further coordinate with the uncoordinated nanocellulose. In other words, the empty coordination orbital of the crosslinking agent of the present embodiment is provided by a metal ion with a valence greater than or equal to two.
[0025] In some embodiments, the transition metal ion is selected from one or any combination of iron ions and copper ions, and the alkaline earth metal ion is selected from one or any combination of calcium ions and magnesium ions.
[0026] In some embodiments, the amount of the cross-linking agent added is (0.1-50) mmol / g of absolute dry nanocellulose. Preferably, the amount of the cross-linking agent added is 1 mmol / g of absolute dry nanocellulose.
[0027] In some embodiments, a crosslinking agent solution is added to the mixed solution and stirred uniformly to obtain a papermaking aid based on nanocellulose, wherein the stirring speed of the uniform stirring is 50 to 1000 r / min and the time is 0.1 to 10 min. Specifically, a crosslinking agent solution is added to the mixed solution and stirred uniformly to obtain a layered liquid, wherein the upper layer of the layered liquid is a clear colorless solution and the lower layer is a white precipitate of a papermaking aid based on nanocellulose.
[0028] The nanocellulose-based papermaking additive prepared in this scheme is a flocculent obtained by coordinating nanocellulose with a filler and a cross-linking agent.
[0029] The nanocellulose-based papermaking aid prepared in this solution can be directly added to paper pulp as a papermaking aid, which can simultaneously improve the filler retention rate and the mechanical properties of paper, so that the mechanical properties of the paper prepared after adding the paper pulp of this solution are good.
[0030] Compared with the prior art, this technical solution has the following characteristics and beneficial effects:
[0031] The nanocellulose-based papermaking additive prepared by the technical solution can achieve the improvement of filler retention rate and paper mechanical properties at the same time at a lower dosage. This is because the nanocellulose first forms a preliminary floc with the filler, and after the cross-linking agent is added, a cross-linked network is formed in the filler. The filler is wrapped with nanocellulose on the outside and can be fully combined with the pulp fiber, solving the problem that the traditional low aspect ratio cellulose nanofibers are less retained in the paper and difficult to form a continuous network structure. The prepared papermaking additive can be directly added to the pulp without the need for drying and crushing operations, which simplifies the application process of the papermaking additive and improves production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Filler-Flow chart for the preparation of high-charge cellulose nanofiber composite filler.
[0033] Figure 2 This is a physical picture of calcium carbonate and calcium carbonate-high-charge cellulose nanofiber composite fillers.
[0034] Figure 3 This is the particle size distribution diagram of calcium carbonate and calcium carbonate-TEMPO oxidized nanocellulose composite fillers.
[0035] Figure 4 Scanning electron microscope (SEM) images of calcium carbonate and calcium carbonate-TEMPO oxidized nanocellulose composite fillers.
[0036] Figure 5 This is a physical picture of the composite filler composed of other fillers and high-charge cellulose nanofibers. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0038] Example 1 Preparation of calcium carbonate-high charge cellulose nanofiber material:
[0039] Preparation of calcium carbonate-high charge cellulose nanofiber material: Add 4g of calcium carbonate to 100g (solid content 0.1%) of dispersed high charge cellulose nanofiber suspension and mix, then add 1mL of 0.1mol / L calcium chloride solution to the mixed solution, and evenly disperse at 500r / min to obtain calcium carbonate-high charge cellulose nanofiber composite filler.
[0040] It should be noted that, in this scheme, maleic anhydride esterified nanofibers, TEMPO oxidized nanofibers and phosphorylated cellulose are selected as the cellulose of the high-charge cellulose nanofiber suspension, and calcium carbonate-maleic anhydride esterified nanofiber composite filler, calcium carbonate-TEMPO oxidized nanofiber composite filler and calcium carbonate-phosphorylated cellulose nanofiber composite filler are prepared respectively.
[0041] The preparation principle diagram of the calcium carbonate-high-charge cellulose nanofiber composite filler in Example 1 is as follows Figure 1 The final preparation of calcium carbonate-high charge cellulose nanofiber composite filler is shown in Figure 2 As shown in the figure, compared with ordinary calcium carbonate suspension, the flocculation of high-charge cellulose nanofibers and the addition of calcium ions to strengthen cross-linking have resulted in significant flocculation. The particle size distribution of calcium carbonate and calcium carbonate-TEMPO oxidized nanocellulose composite fillers was tested, and the test results are shown in the figure. Figure 3 As shown, the particle size of calcium carbonate is between 1-10 μm, and the particle size of calcium carbonate-high-charge cellulose nanofiber composite filler is between 100-400 μm, and the flocculation effect is obvious.
[0042] Scanning electron microscopy observations of calcium carbonate and calcium carbonate-TEMPO oxidized nanocellulose composite fillers showed that Figure 4 As shown, Figure 4 (a) in the equation corresponds to calcium carbonate. Figure 4 The calcium carbonate-TEMPO oxidized nanocellulose composite filler corresponding to (b) in the figure has a calcium carbonate size of about 5 μm and an average composite filler size of about 200 μm, which is consistent with the observed particle size distribution. The surface of calcium carbonate is rough, while the surface of the composite filler is evenly coated with a layer of cellulose nanofibers. The above experimental results all prove that the use of high-charge cellulose nanofibers and the addition of calcium ions can effectively flocculate calcium carbonate and evenly coat the surface of calcium carbonate with a layer of cellulose nanofibers.
[0043] Example 2 Calcium carbonate retention rate and mechanical properties test of paper containing calcium carbonate-high charge cellulose nanofiber composite filler:
[0044] Weigh 0.772g of calcium carbonate-high-charge cellulose nanofiber composite filler (including calcium carbonate-maleic anhydride esterified nanofiber composite filler, calcium carbonate-TEMPO oxidized nanofiber composite filler and calcium carbonate-phosphorylated cellulose nanofiber composite filler) and 1.111g of pulp with a beating degree of 35°SR (coniferous pulp: broadleaf pulp mass is 1:4) and evenly disperse them in 5L of water. Filter the filter cake in a paper sheet former and use a vacuum hot press to hot press at 105°C and 93Pa to obtain paper containing calcium carbonate-high-charge cellulose nanofiber composite filler. The performance table of paper with different calcium carbonate-high-charge cellulose nanofiber composite fillers and calcium carbonate is shown in Table 1:
[0045] Table 1 Paper properties of calcium carbonate-high charge cellulose nanofiber composite filler
[0046]
[0047] 注 :This group needs to use cationic polyacrylamide as a retention agent (0.942g), otherwise the calcium carbonate filler will be completely lost during the sheet making process.
[0048] From the data in Table 1, it can be seen that the retention rate of calcium carbonate is obtained by burning paper at 525°C according to TAPPI T211 standard and comparing the quality before and after. The retention rate of calcium carbonate is increased to 90% compared with the retention rate of calcium carbonate alone (61%).
[0049] The tensile index of the obtained paper was tested using a universal tensile testing machine. The tensile index of the paper with calcium carbonate-high-charge cellulose nanofiber composite filler was the highest, much higher than that of the paper with only calcium carbonate (20.1N·m·g -1 ).
[0050] The above data all indicate that the prepared calcium carbonate-high-charge cellulose nanofiber composite filler can achieve a high calcium carbonate retention rate while enhancing mechanical properties, and has good application prospects.
[0051] Example 3
[0052] The preparation method of the filler and the paper sheeting and testing operation method are the same as those in Example 1 and Example 2, except that the filler, cellulose nanofiber and crosslinking agent are selected as follows: magnesium hydroxide, kaolin, zeolite, calcium carbonate-phosphorylated cellulose nanofiber-ferric ion, magnesium hydroxide-TEMPO oxidized cellulose nanofiber-calcium ion, titanium dioxide-maleic anhydride esterified cellulose nanofiber-aluminum ion, zeolite-carboxymethylated cellulose nanofiber-magnesium ion, and the corresponding filler flocculation before and after photos are shown in FIG. Figure 5 The paper properties of different fillers-high charge cellulose nanofiber composite fillers are shown in Table 2:
[0053] Table 2 Paper performance of different fillers-high charge cellulose nanofiber composite fillers
[0054]
[0055] From the data in Table 2, it can be seen that this method is applicable to a variety of different fillers and different cross-linking agents, and can achieve high filler retention while enhancing mechanical properties.
[0056] Comparative Example 1:
[0057] Source [a]: Other conditions were the same as those in Example 1 and Example 2, except that 20 g of high-charge cellulose nanofibers (solid content 0.5%) and 200 g of calcium carbonate suspension (solid content 2%) were taken and mixed. The paper tensile index and calcium carbonate retention rate of the paper added with the papermaking additives from different sources and Example 1 were tested, and the corresponding performance results are shown in Table 3.
[0058] Table 3 Comparison of different operation processes on filler retention and enhanced mechanical properties
[0059]
[0060] From the data in Table 3, it can be seen that this process can be directly used for filler powder mixing and maintain the stability of the system during papermaking, thereby improving the retention of fillers and cellulose nanofibers and significantly improving the mechanical properties of paper.
[0061] Comparative Example 2
[0062] The preparation of the composite filler is the same as that of Examples 1 and 2, except that no crosslinking agent is added during the preparation of the composite filler in Comparative Example 2. The effects of the composite fillers obtained in Example 1 and Comparative Example 2 on paper properties are shown in Table 4:
[0063] Table 4 Effect of adding cross-linking agent on paper performance
[0064]
[0065] It can be seen from Table 4 that the calcium carbonate-TEMPO oxidized cellulose nanofiber composite filler prepared by the present invention has improved calcium carbonate retention rate and tensile index compared with that without adding a crosslinking agent. This shows that adding a crosslinking agent can effectively help retain fillers and cellulose nanofibers and enhance the mechanical properties of paper.
[0066] The above embodiments only express one implementation mode of the present application, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A method for preparing a papermaking auxiliary agent based on nanocellulose, characterized in that: The following steps are involved: The nanocellulose solution is diluted to a target concentration, and filler powder is added to the nanocellulose solution to obtain a target mixed solution; A crosslinking agent solution is added to the mixed solution and stirred uniformly to obtain a papermaking additive based on nanocellulose, wherein the crosslinking agent in the crosslinking agent solution includes metal ions that provide empty coordination orbitals for chelating with polar groups on the nanocellulose to enhance the performance of the paper additive.
2. The method for preparing a papermaking aid based on nanocellulose according to claim 1, characterized in that: The following steps are involved: The nanocellulose in the nanocellulose suspension is selected from one or a combination of enzymatic cellulose nanofibers, acid hydrolyzed cellulose nanofibers, APS oxidized cellulose nanofibers, TEMPO oxidized cellulose nanofibers, carboxymethylated cellulose nanofibers, periodate oxidized cellulose nanofibers, maleic anhydride esterified cellulose nanofibers, and phosphorylated cellulose nanofibers.
3. The method for preparing a papermaking aid based on nanocellulose according to claim 1, characterized in that: The length to diameter ratio of the nanocellulose in the nanocellulose suspension is greater than 150, and the diameter is less than 20 nm.
4. The method for preparing a papermaking aid based on nanocellulose according to claim 1, characterized in that: The filler in the filler suspension is selected from one or a combination of calcium carbonate, magnesium carbonate, talc, titanium dioxide, calcium silicate, barium sulfate, dolomite, white carbon black, bentonite, polymer particles, zeolite, gypsum, vermiculite, sepiolite, diatomaceous earth, halloysite, tremolite, magnesium hydroxide, aluminum hydroxide, and kaolin.
5. The method for preparing a papermaking aid based on nanocellulose according to claim 1, characterized in that: The empty coordination orbital of the cross-linking agent is provided by a metal ion with a valence greater than or equal to divalent, and the cross-linking agent is selected from a transition metal ion or an alkaline earth metal ion.
6. The method for preparing a papermaking aid based on nanocellulose according to claim 1, characterized in that: The added amount of the cross-linking agent is (0.1-50) mmol / g of absolute dry nanocellulose.
7. The method for preparing a papermaking aid based on nanocellulose according to claim 1, characterized in that: The cellulose concentration of the nanocellulose suspension is (0.02-3.5 g) / 100 mL of water, and the filler concentration of the filler suspension is (0.1-50) g / 100 mL of water.
8. The method for preparing a papermaking aid based on nanocellulose according to claim 1, characterized in that: The nanocellulose suspension is mixed with the filler to obtain a mixed solution, which is a flocculent suspension containing preliminary floccules. The mixing method is selected from one or a combination of mechanical stirring, magnetic stirring, ultrasonic mixing, bubbling mixing, high-pressure homogenization, and convection mixing.
9. A papermaking aid based on nanocellulose, characterized in that: The papermaking aid based on nanocellulose is prepared according to the preparation method of any one of claims 1 to 8, wherein the nanocellulose is coordinated with the filler and the cross-linking agent to obtain floccules.
10. A method for applying a papermaking auxiliary agent based on nanocellulose, characterized in that: The nanocellulose-based papermaking aid described in claim 9 is applied to pulp and papermaking scenarios.
Citation Information
Patent Citations
Grinding calcium carbonate suspension production process, grinding calcium carbonate suspension and paper
CN104343043B
Preparation method of nanocellulose-containing powder
CN111138719A
Preparation method of efficient reinforcing retention aid containing nanocellulose and application of efficient reinforcing retention aid in papermaking
CN117604812A
Ternary particle retention and drainage aid system
CN106368060A
Novel papermaking filler and preparation method for same
CN106917320A